Effects of reindeer on the re-establishment of Betula pubescens subsp. czerepanovii and Salix phylicifolia in a subarctic meadow - Herder, Michael den; Niemelä, Pekka (Rangifer, 2003)
The effect of reindeer browsing on the regeneration of Betula pubescens subsp. czerepanovii and Salix phylicifolia was studied in a subarctic meadow in Finnish Lapland. The aim of the study was to see whether tree recovery from seeds is possible under heavy reindeer-browsing pressure. After removal of the ground and field layer vegetation in 1986, two exclosures were established so that the effect of reindeer on the secondary succession, starting from seeds, could be studied. The size and the number of B. pubescens and S. phylicifolia were recorded in 1994, 1996, 1997 and 1999. Reindeer significantly reduced the height and the number of saplings (plants > 10 cm high) of B. pubescens and S. phylicifolia but the number of seedlings (plants < 10 cm high) did not differ between browsed and unbrowsed plots. Furthermore the heightclass distribution of saplings was different inside the exlosures compared to control areas. Over time browsed plots continued to have high densities of small saplings while in protected plots an increasing number of larger saplings appeared. In our study site, regeneration from seeds seemed possible although the height of B. pubescens and S. phylicifolia was limited by reindeer.